2014
DOI: 10.1021/cn500053d
|View full text |Cite
|
Sign up to set email alerts
|

Silicon-Containing GABA Derivatives, Silagaba Compounds, as Orally Effective Agents for Treating Neuropathic Pain without Central-Nervous-System-Related Side Effects

Abstract: Neuropathic pain is a chronic condition resulting from neuronal damage. Pregabalin, the (S)-isomer of 3-isobutyl-γ-aminobutyric acid (GABA), is widely used to treat neuropathic pain, despite the occurrence of central nervous system (CNS)-related side effects such as dizziness and somnolence. Here we describe the pharmacology of novel GABA derivatives containing silicon–carbon bonds, silagaba compounds. Silagaba131, 132, and 161 showed pregabalin-like analgesic activities in animal models of neuropathic pain, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…13,14) In our previous work, we evaluated the analgesic action of novel GABA derivatives containing silicon-carbon bonds and pregabalin in the PSL model (so-called Seltzer model) and the SNL model (so-called Chung model). 10,15) In those studies, we found that orally administered pregabalin significantly increased the withdrawal threshold not only on the ipsilateral operated side (anti-allodynic effect), but also on the contralateral nonoperated side. This increase of pain threshold on the contralateral side, which was observed with a delay compared to the ipsilateral side, can be considered as representing hypoalgesic action due to excessive sedative action on the pain-related higher centers after distribution of pregabalin into the brain.…”
Section: Resultsmentioning
confidence: 82%
“…13,14) In our previous work, we evaluated the analgesic action of novel GABA derivatives containing silicon-carbon bonds and pregabalin in the PSL model (so-called Seltzer model) and the SNL model (so-called Chung model). 10,15) In those studies, we found that orally administered pregabalin significantly increased the withdrawal threshold not only on the ipsilateral operated side (anti-allodynic effect), but also on the contralateral nonoperated side. This increase of pain threshold on the contralateral side, which was observed with a delay compared to the ipsilateral side, can be considered as representing hypoalgesic action due to excessive sedative action on the pain-related higher centers after distribution of pregabalin into the brain.…”
Section: Resultsmentioning
confidence: 82%
“…A preliminary study was conducted to determine the appropriate dose of pregabalin to induce dizziness. Based on previous studies on the use of pregabalin in rats, experiments were conducted using dosages of 50–200 mg/kg/day . These were the same doses used to achieve an analgesic effect against neuropathic pain in previous studies .…”
Section: Methodsmentioning
confidence: 99%
“…Further optimization of the series led to the development of compounds 160 and 161 . In rotarod experiments, rats administered with pregabalin lost their balance, showing CNS side effects.…”
Section: Silicon-containing Amino Acidsmentioning
confidence: 99%
“…158 Marutake et al synthesized and evaluated the silicon analogs of pregabalin (Figure 42). 159,160 Pregabalin is an analog of γaminobutyric acid (GABA), a neurotransmitter present in the central nervous system. It is used to treat epilepsy and neuropathic pain.…”
Section: Journal Of Medicinal Chemistrymentioning
confidence: 99%